EDUKASI IBU MENYUSUI DALAM MENINGKATKAN KELANCARAN ASI DENGAN PIJAT OKSITOSIN DI DESA GAMPONG UJUNG BATEE KECAMATAN MASJID RAYA KABUPATEN ACEH BESAR - Fitriyanti Fitriyanti; Raudhatun Nuzul ZA; Ulfa Husna Dhirah (Universitas Ubudiyah Indonesia, 2025)
Breast milk (ASI) production is often hindered by a lack of oxytocin hormone stimulation and limited knowledge among breastfeeding mothers about how to improve milk flow. One effective non-pharmacological method to enhance breast milk production is oxytocin massage, a massage technique along the spine that stimulates the release of the oxytocin hormone. This community service activity aimed to increase the knowledge and skills of breastfeeding mothers in performing oxytocin massage to promote breast milk production. The activity was conducted in Gampong Ujung Batee Village, Masjid Raya Subdistrict, Aceh Besar District, in September 2025. The implementation methods included health education sessions, oxytocin massage demonstrations, and hands-on practice guided by the implementing team. The participants consisted of 15 breastfeeding mothers and community health volunteers (posyandu cadres). The results showed an 80% increase in the mothers’ knowledge of the benefits and techniques of oxytocin massage after the educational intervention. In addition, most participants reported smoother breast milk flow within 2–3 days of routinely performing oxytocin massage. This activity had a positive impact on improving the understanding of breastfeeding mothers regarding the importance of oxytocin hormone stimulation for successful breastfeeding. It is expected that similar programs can be sustainably implemented by health workers and community cadres in the area.